2014
DOI: 10.1177/0141076814530686
|View full text |Cite
|
Sign up to set email alerts
|

Medical relevance of UK-funded non-human primate research published from January 1997 to July 2012

Abstract: In 2012, the Bateson Review of research using non-human primates (NHPs) recommended the commissioning of a working group to identify and follow-up the results of UK-funded NHP research of potential benefit for human health (Recommendation 4), but the Medical Research Council (MRC) has postponed implementation of the recommendation. Information on results and potential benefits of NHP research therefore remains unavailable. To fill this gap in knowledge, this study identified all published NHP research studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Non-human primates, including monkeys, are genetically similar to humans compared to other experimental animals, making the simulation of human pathology and physiology relatively accurate. However, their high cost, low reproducibility and ethical concerns severely limit their use as experimental models (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Non-human primates, including monkeys, are genetically similar to humans compared to other experimental animals, making the simulation of human pathology and physiology relatively accurate. However, their high cost, low reproducibility and ethical concerns severely limit their use as experimental models (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the "effectiveness of knowledge transfer from basic to applied research" -something frequently claimed to be beyond doubt and, indeed, "the only way to successfully cope with devastating disorders and reduce the invasive character of many clinical procedures applied for their diagnosis and treatment" (17) -has been questioned by many (e.g. 18). This is acknowledged by Recommendation 4 of the Bateson Review, which suggests developing a mechanism "…to identify research results with potential to deliver improvements to healthcare or other significant benefits to society, and to assess the extent to which the potential benefits are achieved".…”
Section: Introductionmentioning
confidence: 99%
“…This is acknowledged by Recommendation 4 of the Bateson Review, which suggests developing a mechanism "…to identify research results with potential to deliver improvements to healthcare or other significant benefits to society, and to assess the extent to which the potential benefits are achieved". Unfortunately, three years later, at the time of writing, the Medical Research Council (MRC) has indicated that this recommendation "is not currently being taken forward, as we have prioritised work on other recommendations in the Bateson Review" (18). Factual information on NHP research results and their medical relevance (as opposed to claims of efficacy and human relevance by NHP researchers) therefore remains unavailable to the public and the wider medical profession.…”
Section: Introductionmentioning
confidence: 99%